2007
DOI: 10.4161/cbt.6.11.4874
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of single agent Val-boroPro (talabostat) inhibiting fibroblast activation protein in patients with metastatic colorectal cancer

Abstract: Purpose: Fibroblast Activation Protein (FAP) is a tumor fibroblast protease that has been shown to potentiate colorectal cancer growth. The clinical impact of FAP inhibition was tested using Val-boroPro (Talabostat), the first clinical inhibitor of FAP enzymatic activity, in a phase II study of patients with metastatic colorectal cancer.Methods: Patients with metastatic colorectal cancer who had previously received systemic chemotherapies were treated with single agent Val-boroPro 200 μg p.o. BID continuously.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
167
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(178 citation statements)
references
References 46 publications
1
167
0
1
Order By: Relevance
“…Recent years have brought a strong interest in DPPIV and its homologs, which led to the development of numerous highly selective and potent DPP inhibitors. For example, DPPIV-selective inhibitors, Sitagliptin and Vildagliptin, are already used for the treatment of diabetes (48), whereas the broad range DPP inhibitor, PT-100, has been tested in clinical trials for various types of cancer (20,21,49). Using such potent inhibitors in an appropriate treatment regime may allow overcoming or avoiding induction of DPPs observed in P32/98-treated tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have brought a strong interest in DPPIV and its homologs, which led to the development of numerous highly selective and potent DPP inhibitors. For example, DPPIV-selective inhibitors, Sitagliptin and Vildagliptin, are already used for the treatment of diabetes (48), whereas the broad range DPP inhibitor, PT-100, has been tested in clinical trials for various types of cancer (20,21,49). Using such potent inhibitors in an appropriate treatment regime may allow overcoming or avoiding induction of DPPs observed in P32/98-treated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing interest in these potential therapeutic targets led to the development of numerous DPP inhibitors. For example, a broad range DPP inhibitor, PT-100, has already been tested in clinical trials for the treatment of various cancers (20,21). Surprisingly, however, this compound was introduced to clinics without knowledge of the exact mechanisms of its actions, which ultimately led to the failure of these trials.…”
mentioning
confidence: 99%
“…In clinical trials, Phase II trial of Val-boro-Pro demonstrates minimal clinical activity in patients with previously treated metastatic colorectal cancer. 56 In addition, Phase II trial of talabostat and docetaxel in advanced non-small cell lung cancer shows no evidence that talabostat enhanced the clinical activity of docetaxel in patients with NSCLC. 57 PT630 is more specific than talabostat, effectively inhibiting FAP and DPPIV but not the intracellular family members.…”
Section: Clinical Applications Of Fapmentioning
confidence: 99%
“…However, a clinical trial on CRC patients using talabostat, an inhibitor of FAP-enzymatic activity, showed a minimal clinical effect, and the authors suggest that the partial inhibition may be due to another contributing factor or factors. 14 In the present study, we used FAP as a marker of activated fibroblasts to investigate their occurrence in various lesions of the adenoma-carcinoma sequence in human CRC. Further in vitro studies analyzed fibroblast activation in co-culture experiments.…”
mentioning
confidence: 99%